Pencarian Rute Terpendek Menggunakan Algoritma Bellman-Ford (Studi Kasus: PT. JNE Medan) - Ester Tetri H Hutasoit (Universitas Budi Darma, 2019)
Every human being wants to get to his destination on time. But often congestion causes human desires are blocked. Therefore, we need a way to overcome this problem by knowing the minimum distance to reach a place. The service sector is a field that offers services by helping consumers in various ways. The service sector is a field that will never experience bankruptcy even in difficult conditions because everyone certainly needs the help of others in completing or completing various things. Freight forwarding services are one of the services most widely used, especially in saving time and costs (cost). In the freight forwarding service, the route of shipping the goods becomes very important because without a structured route, the delivery of goods becomes not timely and can be detrimental to the company itself. The loss that will be experienced by the company is that the delivery time will be longer because the delivery distance will be further. In this study the calculation of the application using the Bellman-Ford algorithm is performed which aims to find the shortest path from the office of PT. JNE Medan to Helvetia. The algorithm used is Bellman-Ford. The Belmman-Ford algorithm is used to calculate all paths from origin to destination formed in a graph to find the shortest path.